2010
DOI: 10.1016/j.neuroscience.2010.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Incubation of conditioned fear in the conditioned suppression model in rats: role of food-restriction conditions, length of conditioned stimulus, and generality to conditioned freezing

Abstract: We recently adapted the conditioned suppression of operant responding method to study fear incubation. We found that food-restricted rats show low fear 2 days after extended (10 d; 100 30-sec tone-shock pairings) fear training and high fear after 1-2 months. Here, we studied a potential mechanism of fear incubation: extended food-restriction stress. We also studied whether fear incubation is observed after fear training with a prolonged-duration (6-min) tone conditioned stimulus (CS), and whether conditioned f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 37 publications
6
44
0
Order By: Relevance
“…2, 4) that remained stable, while repeatedly shocked rats displayed an increase in fear across the extended memory retention interval. This pattern in multitrial conditioned animals is consistent with evidence of incubation using overtraining with an auditory CS (8-100 trials), spaced over multiple days (2 or 10 d) and/or under food deprivation (Houston et al 1999;Pickens et al 2010). Here, we demonstrate using a more reduced conditioning preparation that a single trial does not yield fear incubation, but two conditioning trials within a single session were sufficient to generate a time dependent increase in context fear expression.…”
Section: Discussionsupporting
confidence: 73%
“…2, 4) that remained stable, while repeatedly shocked rats displayed an increase in fear across the extended memory retention interval. This pattern in multitrial conditioned animals is consistent with evidence of incubation using overtraining with an auditory CS (8-100 trials), spaced over multiple days (2 or 10 d) and/or under food deprivation (Houston et al 1999;Pickens et al 2010). Here, we demonstrate using a more reduced conditioning preparation that a single trial does not yield fear incubation, but two conditioning trials within a single session were sufficient to generate a time dependent increase in context fear expression.…”
Section: Discussionsupporting
confidence: 73%
“…This is the standard protocol that has been used repeatedly for pharmacological testing and investigations into the time-course and mechanisms underlying fear incubation (Pickens et al, 2009a; Pickens et al, 2009b; Pickens et al, 2010). It has reliably produced fear incubation under a wide variety of feeding conditions and after other manipulations were given (e.g.…”
Section: Basic Protocol 1: Concurrent Freezing/conditioned Suppressiomentioning
confidence: 99%
“…However, it is also possible to cause incubation of a more diffuse emotional state by pairing longer cues (minutes long) with unpredictable shocks (proposed to model “conditioned anxiety”) (Pickens et al, 2010). The procedure is very similar to those used in the basic protocol (see Figure 1), with differences in the length of the tone cue and the timing of the shocks.…”
Section: Alternate Protocol 1: Fear/anxiety Incubation With Long Cuesmentioning
confidence: 99%
“…A second difference is that we used a conditioned suppression procedure to evaluate conditioned fear whereas the former studies used a conditioned freezing procedure. Freezing, by definition, prevents lever pressing and previous studies have shown that conditioned freezing and conditioned suppression are correlated (e.g., Pickens, et al, 2010). Additional studies using lesioning have shown that the dependencies of these two behaviors on the basolateral and central nuclei of the amygdala, and the ventral periaqueductal grey differs (Amorapanth et al, 1999;Lee, et al, 2005;McDannald, 2010;;McDannald and Galarce, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that the conditioned suppression model is in contrast to conditioned freezing methods. While freezing would necessarily constitute response suppression, studies have shown that the suppression model involves additional conditioned fear processes (Amorapanth et al, 1999;Lee, et al, 2005;McDannald, 2010;Pickens, et al, 2010;McDannald and Galarce, 2011). 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 8 Clinically, the defining characteristics for the classification of mTBI are almost entirely based on signs or symptoms and include a relatively broad range of severity (Defense and Veterans Brain Injury Center, 2006).…”
Section: Introductionmentioning
confidence: 99%